The effect of reinforcement ratio cantula fiber (Agave cantula roxb) on tensile strength of textile reinforced concrete. (October 2019) - Purwanto, E; Kristiawan, S A; Safitri, E; Sasmito, A N
Abstract: Cantula Fiber (Roxb Agave Cantula) is a natural fiber that can be developed as a reinforcement material in concrete and can be applied to structural and nonstructural elements of a building. This research aimed to test the direct tensile strength of polymer modified mortar by strengthening cantula fiber in various forms of cantula fiber reinforcement ratios. Test specimens were in the form of polymer modified mortar with reinforced woven fiber and short fiber as textile reinforced concrete (TRC). Specimens used were in the form of plates measuring 12 mm x 80 mm x 400 mm with variations in fiber reinforcement ratios of 1.5%, 2.5%, 3.5%, and 4.5%. Test specimens were tested at age of 3 days and 28 days. The results of the test showed the highest increase in the reinforcement ratio of 4.5% in the PMM specimen with a tensile strength value of 2.41 MPa at 3 days and at 3.41 MPa at 28 days. Meanwhile, the value of the largest tensile strength in TRC was found on the reinforcement ratio of 3.5% with a tensile strength of 2.95 MPa at 3 days and 3.38 MPa at 28 days. Therefore, the effective reinforcement ratio ranged from 3.5% to 4.5%.